STRATEGI PEMASARAN SPONSORSHIP EVENT DAN ENDORSEMENT SELEBRITI DALAM MENINGKATKAN BRAND AWARENESS - Eji, Azizah (Airlangga Journal of Innovation Management, 2024)
This research was conducted to examine the influence of event sponsorship on brand awareness. Addressing this theme in a journal is of significant value in terms of contributing to industry understanding, knowledge development, and practical applications in brand marketing strategies like Kapal Api. The study employed a qualitative approach by reviewing previous research and relating it to a case study of Kapal Api. Based on the case study of Kapal Api, Indonesian badminton athletes play the role of celebrity endorsers for the Kapal Api brand. The compatibility of a celebrity endorser with a product refers to the alignment of the celebrity's image, values, and behaviors with the desired impression of the advertised brand. The findings of the research indicate that the sponsorship strategy implemented by Kapal Api successfully increased consumer brand awareness, particularly among badminton enthusiasts. The study also demonstrates that the inclusion of celebrity endorsers, specifically badminton athletes, further enhances the success of Kapal Api's event sponsorship strategy. The study highlights the potential effectiveness of sponsorship events and celebrity endorsements in increasing consumer awareness of Kapal Api products. This suggests that implementing these strategies could lead to heightened recognition and visibility for the brand among consumers.